2020
DOI: 10.21203/rs.3.rs-48770/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Challenges and Opportunities of Online Volunteering for COVID-19 Response in Iran: A Qualitative Study

Abstract: Background: The aim of this brief report is to identify the challenges and opportunities of online volunteering to respond to the COVID-19 pandemic from the perspective of the managers of the Iranian Red Crescent Society (IRCS).Methods: In this study we have used a qualitative method including semi-structured interviews for investigating the opportunities and challenges of using virtual volunteers. The eligible participants meeting the inclusion criteria for this study were eight IRCS managers who had used onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
(40 reference statements)
0
8
0
2
Order By: Relevance
“…Finally, a study conducted in Iran during the COVID‐19 pandemic found that online volunteering allows diverse populations to volunteer, including the disabled, the elderly, or people living in nonurban areas. However, this study also found that alternative forms of volunteering reduce commitment to volunteering (Seddighi et al., 2020). While there is some knowledge about the alternative patterns of volunteering, as presented above, the body of comparative researches on the experience of volunteers in alternative patterns of volunteering versus the traditional pattern in routine times is very limited (see, for example, Ihm, 2017).…”
Section: Introductionmentioning
confidence: 60%
“…Finally, a study conducted in Iran during the COVID‐19 pandemic found that online volunteering allows diverse populations to volunteer, including the disabled, the elderly, or people living in nonurban areas. However, this study also found that alternative forms of volunteering reduce commitment to volunteering (Seddighi et al., 2020). While there is some knowledge about the alternative patterns of volunteering, as presented above, the body of comparative researches on the experience of volunteers in alternative patterns of volunteering versus the traditional pattern in routine times is very limited (see, for example, Ihm, 2017).…”
Section: Introductionmentioning
confidence: 60%
“…For instance, older people with lifelong careers in the medical field – such as nurses, doctors, and social workers – volunteered in the medical field or older people helped online as tutors to support families with homeschooling ( Halpern, 2020 ; Sun et al, 2021 ). At the same time, we must remember that there are volunteers, including many older adults, who are unable to fulfill voluntary roles because of pandemic-related stay-at-home regulations and changes in the operations of social services and other nonprofit organizations ( Morrow-Howell et al, 2020 ; Seddighi et al., 2020 ; Sun et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Volunteering is an important activity in the lives of many older adults, but many volunteer opportunities have disappeared with the COVID-19 pandemic (Seddighi et al, 2020). Stay-at-home orders and changes in operations for social services and other nonprofits have meant that many of the in-person volunteer roles filled by older adults are no longer active or older adults are concerned about continuing participation.…”
Section: Introductionmentioning
confidence: 99%